Public Control and Crime Prevention: Interaction at the State and Regional Levels - Prodan, Tetyana; Gryshchenko, Iryna; Yermak, Oleksandr; Ovcharenko, Ruslan; Hadzhiieva, Arzu Bakhruz (Pakistan Journal of Criminology, 2024)
The study aimed to analyse the interaction between civil society and the government in combating crime at the national and regional levels. The research was conducted using the comparative legal method, formal legal method, legal modelling method, and statistical method. The study‟s main conclusion was that at the present stage, any rule-of-law democratic state‟s decisions should consider public opinion and the position of civil society. The state should ensure the responsibility of those responsible for such decisions, including using public control instruments. The article also reveals practical approaches to implementing public control in Ukraine. The study concludes that decentralisation of the law enforcement system of the internal affairs bodies guarantees stable political, social and economic development of the country, provided that the state and society interact and society exercises public control in combating crime. In the future, scientific research may study the forms, methods, and means of implementing the interaction between society and the state in tackling crime.
Keywords: кримінологія; протидія злочинності